Determinant of commercial bank profitability in Malaysia / Amirul Syazwan Anuar - Anuar, Amirul Syazwan (Faculty of Business Management, 2017)
The main purpose of this research is to find out the profitability determinants of commercial bank in Malaysia. 5 commercial banks have been chosen to represent the commercial bank in Malaysia during the time line from 2006 until 2015. ROA was chosen as a dependent variable to estimate the commercial bank’s profit, and 3 independent variables which are liquidity, operating expenses and bank size. After running these data on the data analysis software which is STATA, it is found that only Liquidity and Operating expenses are significant variables while bank size are insignificant in determining the profitability of commercial banks in Malaysia for that time.